Matérialisation d’une représentation holistique du monde dans l’habitat des indigènes guarani au Brésil - Anaïs Guéguen Perrin (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The Anthropocene questions our modes of interaction with the Earth system, calling into question our ways of living and inhabiting. By approaching the paradigm of Buen Vivir Guarani and its materialization in the habitat, it is a question of showing how this one can be considered, beyond the dwelling, in an interrelation with the territory and the non-human. This article is based on field surveys and a complementary literature review to highlight a multi-scalar conception of common.